Tourism Development Trends in the Republic of Armenia After COVID-19 Pandemic and in the Context of Russian-Ukrainian War - Tovmasyan, Gayane («Տնտեսագետ» հրատ․)
Covid-19 pandemic brought many problems to the world. Tourism sphere suffered a lot. In Armenia the number of tourists decreased by 81% in 2020. In 2021 and 2022 tourism sphere began to recover gradually. The Russian-Ukrainian war brought new problems to the world economy. In 2019, Russian spending on travel abroad reached US$ 36 billion and Ukrainian spending US $8.5 billion. Concerning tourism destinations, Russia and Ukraine account for 4% of international tourist arrivals in Europe but only 1% of Europe’s international tourism receipts. The number of Russian tourists to Armenia increased in 2022. The article analyzes the impact of the influx of Russian tourists to the Armenian tourism sector due to the Russian-Ukrainian war. The surveys show that Russian tourists are very satisfied with Armenia, so it is necessary to develop attractive tourist packages to different destinations in Armenia for Russians. The correlation analysis between total tourists of Armenia and restaurants and hotels revenue is 0.52, between total tourists and employment is 0.14 and between total tourists and GDP is 0.37. Tourism should contribute to the sustainable development of the country, so aggressive marketing policies should be implemented to promote incoming tourism in Armenia after pandemic.
Keywords: Markets And Competition